Atypical course of vertebral artery identified by ultrasound prescan before performing a stellate ganglion block - Daeseok Oh; Hyun-Seong Lee (Journal of Medical Ultrasound, 2022)
Ultrasound provides direct visualization of blood vessels and soft tissues around the sympathetic chain and potentially minimizes injury to these critical anatomic structures when performing stellate ganglion block (SGB). We report an atypical left vertebral artery course detected during an ultrasound prescan before performing a SGB. The left vertebral and inferior thyroid arteries were identified on the longus colli muscle's ventral surface at the C6 level. This report was the first to demonstrate ultrasound images of a vulnerable vertebral artery to intravascular injection. The study emphasized the importance of identifying the sonoanatomy before performing procedures involving the anterior cervical vertebrae.